Domains of Discharge Readiness for Patients After Abdominal Surgery: A Qualitative Exploratory Study - Ayodeji Olubunmi Ogunmuyiwa; Chinomso Ugochukwu Nwozichi; Rafiat Ajoke Anokwuru; Modupe Oyeronke Okenla; Deborah Tolulope Esan; Carlos Guillermo Ramos (Nursing Open)
ABSTRACT Aim To explore the domains of discharge readiness among patients following abdominal surgery. Design A qualitative exploratory study. Methods Data were collected through semi‐structured interviews involving patients, caregivers, and healthcare providers (clinical nurses and surgeons) engaged in abdominal surgical care. A total of 19 participants contributed to the study through four focus group discussions and four individual interviews. Data were analysed using content analysis. The study adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results Five key dimensions of discharge readiness were identified: physical readiness, knowledge/information readiness, psychological readiness, social readiness, and spiritual readiness. Each domain includes specific factors that influence a patient's preparedness to transition safely and effectively from hospital to home. Patient Contribution Patients and caregivers provided valuable insights into the core domains of discharge readiness through their active participation in this study.